METODOLOGI PEMIKIRAN HUKUM AL-SHA’RANI DAN KONTRIBUSINYA DALAM MENJAGA KERUKUNAN UMAT ISLAM - M. Adib Hamzawi (Jurnal Ilmu Hukum, 2024)
This study aims to explain and describe the legal thinking of al-Sha'rani in terms of maintaining harmony in the Muslim community. Abdul Wahhab al-Sha'rani (d.1565 AD) was one of the scholars from Egypt who was affiliated with the Shafi'i school of thought. He is known for his thoughts in the fields of fiqh and Sufism. Imam al-Sha'rani's thoughts appear to be inclusive, namely trying to harmonize various perspectives on Islamic law without leaving the depth of spirituality that is the hallmark of Sufism. His works discuss the importance of implementing sharia law within a deep spiritual framework. Al-Sha'rani combines aspects of fiqh law and the esoteric dimensions of Sufism in a balanced framework of thought. The results of the study, al-Sha'rani's methodology of thought is inclusive and reconciliatory, where he tries to balance between sharia and nature, between worldly and hereafter needs, and between aspects of external law and inner spirituality. In detail, al-Sya'rani's methodology of thought is classified into four main ideas. First, the division of various legal fatwas into two large poles, namely 'azimah and rukhsah or tasydid and takhfif which must be taken by Muslims according to their individual situations. This illustrates the flexibility in the application of sharia according to the conditions of each individual. Second, acceptance of all schools of thought and their variations in law. All views from various schools of thought are correct and valid as long as they are based on the text. No opinion is more correct than another, but the differences are only based on the social needs and physical conditions of the individual. This concept is important to prevent division among Muslims. Differences of opinion among scholars are a blessing and not a problem. The use of the metaphor of a large tree where each branch is an opinion of a scholar rooted in sharia aims to unite various views of fiqh in order to create harmony. Third, the integration of the physical dimension (sharia which is carried out outwardly based on fiqh) and the inner (the essence contained in the inner spirituality based on Sufism) in religion.